PENGEMBANGAN LKPD BERBASIS CREATIVE PROBLEM SOLVING PADA MATERI FUNGSI UNTUK KELAS X SMA/MA - Johan Irawan (Departemen Matematika, 2020)
This study aims to develop student worksheets based on the Creative Problem Solving on mathematics functional material for class X MIPA Senior High School students. This research design uses the Plomp development model which consists of three stages, namely the preliminary research stage, the development / prototyping stage, and the assessment stage. In the preliminary research, needs analysis, curriculum analysis, concept analysis, and student analysis are carried out which are useful for obtaining characteristics in the form of learning tools developed. In the prototype development / development stage, a learning device prototype design was made in the form of student worksheets for mathematics functions material. Prototypes must go through formative evaluation in the form of self-evaluation and expert evaluation to get a valid prototype. The last stage is the assessment, this assessment aims to determine the practicality criteria for the LKPD prototype which is carried out after a one to one evaluation. This research was conducted when Covid-19 was pandemic, so there were several stages of research that could not be carried out properly. The conclusion of this study is to obtain student worksheets based on Creative Problem Solving on the functional material in the form of lesson plans and worksheets which are categorized as valid and practical. Kata kunci — Development Research, Student Worksheet, Creative Problem Solving